BUILDING STUDENTS' RELIGIOUS CHARACTER IN THE INTEGRATION OF DINIYAH AND INDEPENDENT CURRICULUM AT INTEGRATED SMK AL ISHLAHIYAH SINGOSARI MALANG - Ma'rufah, Siti; Hakim, Dian Mohammad; Hidayatullah, M. Fahmi (Faculty of Administrative Science, Universitas Brawijaya, 2024)
Research on the integration of the diniyah and independent curriculum in PAI learning to build students' religious character at Al Ishlahiyah Singosari IntegratedVocational School in Malang, this aims to describe and analyze a design,implementation and evaluation of the integration of the diniyah and Merdekacurriculum. This type of research is qualitative research, based on the discussionincluding descriptive research using a case study plan. Data collection techniquesuse observation, interviews, and documentation. Data analysis is carried outstarting from data condensation, data presentation, and conclusion drawing. Theresults showed that the design of the integration of the diniyah and independentcurriculum is classified as a separate model (Fragmanted model) because itdescribes that science is separated and has its own character about deep andcomprehensive understanding. Implementation of the integration of the diniyahand Merdeka curriculum through the principle of reflective learning. The divisionof learning time is in the morning for the Merdeka curriculum, while the duhurtime, for the diniyah curriculum. Evaluation in this integration refers to evaluationsthat are Formative (initial assessment / learning process), Summative (PTS, PAS,PAT), monthly meetings, annual work meetings and workshops to increaseeducational effectiveness in producing graduates with Islamic character.